Analysis Pragmatical Policy of Leadership Style Dynamics - Jamaluddin, Muhammad Iqbal; Herawan, Endang; Rahyasih, Yayah; Pribadi, Luthfi Audia (Future Science / FSH-PH Publications, 2023)
Pragmatic policy is a type of policy that prioritizes practicality and usefulness. Decision-making from this pragmatic policy has an impact on overlapping policies so that a suitable leadership style is needed to anticipate these policies. The purpose of this research is to analyze the appropriate and proportionate way of leadership style to anticipate pragmatic policies. method used. This research is a qualitative method with a phenomenological approach. This research was conducted in the Men's Dormitory of Middle and High School Alexandria International Islamic School with a sample of 2 people. The instruments used are observation, interviews and documentation studies. The results showed that the situational leadership style and delegative democracy were the most proportional and suitable leadership styles in accommodating crucial, fast and pragmatic policies. This has an impact on the consideration of policy implementation that is right on target and applied properly so that each line of coordination can display the best contribution to policy.